STRENGTHENING THE VALUE OF RELIGIOUS MODERATION THROUGH PAI-BP LEARNING - Aisyah, Siti; Setyono, Hendri; Suhendi, Endi (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This study is motivated by the many intolerant attitudes of students, the strengthening of the value of religious moderation through learning Islamic religious education and character (PAI-BP) is able to encourage students to be tolerant in education. The purpose of this study was to determine the strengthening of the value of religious moderation through learning Islamic religious education and character (PAI-BP). This research uses a qualitative method with a descriptive Approach. The data collection technique is triangulation. Research based on the philosophy of postpositivism is used to research natural object conditions. The results and conclusions of this study strengthen the value of religious moderation, namely Tawasut, Tawazun, Ta’adul, Tasamuh, Musawah, and Shura. The four stages of pai-bp learning are inserting (insertion) moderation content in each learning material, optimizing learning approaches that can give birth to critical thinking, respecting differences, respecting other people’s opinions, being tolerant, democratic, daring to convey ideas, being sportive and responsible, organizing certain training and debriefing education programs with special themes about religious moderation, and reaching evaluation aspects.